Neem, lees … vertolk, bely! Kantaantekeninge by die teologie van Dirkie Smit - Vosloo, RR (Nederduitse Gereformeerde Teologiese Tydskrif, 2007)
This article focuses on the importance of the notions of reading, interpretation and confession in the thought of Dirkie Smit. It is argued that the reading of Scripture is central to Smit’s understanding of the nature and task of theology. Scripture, however, is for Smit to be read and listened to in communion. The article also highlights Smit’s concomitant emphasis on the importance of interpreting the Word responsibly, as well as his call to confess our faith in the light of the Word through timeful embodiment.